B‐Cu‐Zn Gas Diffusion Electrodes for CO(2) Electroreduction to C(2+) Products at High Current Densities - Song, Yanfang (Angew Chem Int Ed Engl, 2021)
Electroreduction of CO(2) to multi‐carbon products has attracted considerable attention as it provides an avenue to high‐density renewable energy storage. However, the selectivity and stability under high current densities are rarely reported. Herein, B‐doped Cu (B‐Cu) and B‐Cu‐Zn gas diffusion electrodes (GDE) were developed for highly selective and stable CO(2) conversion to C(2+) products at industrially relevant current densities. The B‐Cu GDE exhibited a high Faradaic efficiency of 79 % for C(2+) products formation at a current density of −200 mA cm(−2) and a potential of −0.45 V vs. RHE. The long‐term stability for C(2+) formation was substantially improved by incorporating an optimal amount of Zn. Operando Raman spectra confirm the retained Cu(+) species under CO(2) reduction conditions and the lower overpotential for *OCO formation upon incorporation of Zn, which lead to the excellent conversion of CO(2) to C(2+) products on B‐Cu‐Zn GDEs.